Word myths : debunking linguistic urban legends - Wilton, David, 1963- (OUP E-Books., 2004)
Do you ""know"" that posh comes from an acronym meaning ""port out, starboard home""? That ""the whole nine yards"" comes from (pick one) the length of a WWII gunner's belt; the amount of fabric needed to make a kilt; a sarcastic football expression? That Chicago is called ""The Windy City"" because of the bloviating habits of its politicians, and not the breeze off the lake? If so, you need this book. David Wilton debunks the most persistently wrong word histories, and gives, to the best of our actual knowledge, the real stories behind these perennially mis-etymologized words. In addition, he